Adaptive and Sustainable Internal Government Service Governance Strategy to Optimize the Functions of the Household Section of The General Bureau of the Regional Secretary of East Java Province - Vicky Rahmawan Putra; Fedianty Augustinah; Eny Haryati (Dynamics Social : International Journal of Social Sciences and Communication, 2025)
This research seeks to examine adaptive and sustainable internal governance approaches to enhance the operations of the Household Division within the General Bureau at the East Java Province Regional Secretariat. The study concentrates on four main elements: the integration and compatibility of SIM-BMD with financial systems and LPSE, technology-driven centralized logistics frameworks, the execution of asset lifecycle SOPs involving preventive maintenance and quick transfer methods, and the enhancement of human resource capabilities through targeted training and the creation of digital leaders. Employing a qualitative descriptive approach within a case study framework, information was gathered via detailed interviews, participatory observation, and analysis of institutional documents. The results indicate that integrating systems improves transparency, efficiency in reporting, and accountability in asset management. The centralized logistics approach paired with intelligent warehouse techniques greatly enhances distribution efficiency and decreases operational expenses. Additionally, proactive asset lifecycle management reduces the chances of asset deterioration and prolongs its useful life. Nonetheless, inconsistent digital skills among staff continue to pose a significant obstacle, necessitating ongoing training initiatives and guidance. The research suggests promoting a data-centric work environment, inclusive digital advancements, and collaboration among departments to establish a professional, effective, and sustainable internal governance framework consistent with the tenets of good governance and smart government